2015
DOI: 10.1007/s11999-014-3902-5
|View full text |Cite
|
Sign up to set email alerts
|

Do Serologic and Synovial Tests Help Diagnose Infection in Revision Hip Arthroplasty With Metal-on-metal Bearings or Corrosion?

Abstract: Background The diagnosis of periprosthetic joint infection (PJI) in patients with failed metal-on-metal (MoM) bearings and corrosion reactions in hip arthroplasties can be particularly difficult, because the clinical presentation of adverse local tissue reactions may mimic that of PJI, because it can also occur concurrently with PJI, and because common laboratory tests used to diagnose PJI may be elevated in patients with MoM THAs. Questions/purposes We sought to determine the test properties of the serum eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Previous studies have examined the use of preoperative hip aspirations in helping to diagnose periprosthetic joint infections [1,3,25,30,33]. It has been suggested that preoperative aspirations should be performed on select patients with an intermediate to high risk of infection based on clinical and radiographic findings [1,3,14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the use of preoperative hip aspirations in helping to diagnose periprosthetic joint infections [1,3,25,30,33]. It has been suggested that preoperative aspirations should be performed on select patients with an intermediate to high risk of infection based on clinical and radiographic findings [1,3,14].…”
Section: Discussionmentioning
confidence: 99%
“…They reported a 75 % sensitivity and 67 % specificity in diagnosing PJI if both the CRP was >8.0 mg/L and ESR was >22 mm/h [23•]. There have been other case reports of failed MOM articulations masking as infection in the literature as well [32,34].…”
Section: Serum Inflammatory Markersmentioning
confidence: 99%
“…However, MOM articulations can falsely elevate both the white blood cell (WBC) count and neutrophil percentage. Metal particles, degenerating cells, and foreign debris can falsely elevate the WBC count [32]. One study showed that while automated WBC count of >3000 cells/uL was 100 % sensitive for diagnosing PJI, it was only 57 % specific [23•].…”
Section: Aspiration Of the Hip Jointmentioning
confidence: 99%
See 2 more Smart Citations